IMPLEMENTASI STANDAR SARANA DAN PRASARANA PENDIDIKAN PADA MADRASAH ALIYAH NEGERI 3 BANYUWANGI - Siti Aimah; Kholisatur Rohmah (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2020)
The objectives set in this study are: (1) To find out the implementation of Sarpras standards in MAN 3 Banyuwangi; (2) To find out the factors that are the strengths and weaknesses in implementing the standard of education sarpras at MAN 3 Banyuwangi; (3) To find out what factors are the weaknesses in applying educational infrastructure standards in MAN 3 Banyuwangi; (3) To find out the right strategy to be applied in MAN 3 Banyuwangi. This research method uses descriptive qualitative, data collection through interviews, observation and documentation. Data analysis using SWOT analysis and data validity techniques using triangulation. The results of his research: (1) Implementation of standard facilities and infrastructure at MAN 3 Banyuwangi, namely the suitability of facilities and infrastructure at the educational unit level MAN 3 Banyuwangi has 27 study groups. This is in accordance with the standards of Permendiknas Number 24 of 2007 which states that "one SMA / MA has a minimum of 3 study groups and a maximum of 27 study groups"; (2) Supporting factors that are owned are MAN 3 Banyuwangi (86%) facilities and infrastructure in accordance with the education unit so that it helps support the learning process (2) The supporting factor that becomes its strength is the innovation of facilities and infrastructure outside the SNP, opportunities come from government support in the form of APBN funds and new student enrollments are opportunities for the fulfillment of sarpras at MAN 3 Banyuwangi. While the inhibiting factor is weakness, there is still a joint laboratory for practicing biology, chemistry and physics subject matter, and the number of latrines that do not meet the ratio of the number of students. While the threats are the existence of a favorite school around MAN 3 Banyuwangi; (3) Infrastructure Strategy at MAN 3 Banyuwangi; always maintain the existence of madrasas, the need for a team of maintenance and control of sarpras. In addition, it is also necessary to complete the facilities, furniture and practical tools for the laboratory and provide a special place for each laboratory room.